2015
DOI: 10.1128/jcm.01351-15
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of the First Case of Botulism Caused by Clostridium butyricum Type E Toxin in the United States

Abstract: We report here the laboratory investigation of the first known case of botulism in the United States caused by Clostridium butyricum type E. This investigation demonstrates the importance of extensive microbiological examination of specimens, which resulted in the isolation of this organism. B otulism is a rare but acute paralytic disease caused by botulinum neurotoxin (BoNT). Botulism can occur when contaminated food is ingested (food-borne) or when BoNT-producing clostridia colonize wounds or the intestine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Since then, C. butyricum has been associated with botulism in other countries (i.e. China, India, Japan, Ireland, and the USA) [32]. Notably, the operon encoding the BoNT/E toxin harboured by the neurotoxigenic C. butyricum strains is very similar to that carried by group II type E toxin-producing C. botulinum strains [33].…”
Section: Pathogenic Botulismmentioning
confidence: 98%
See 1 more Smart Citation
“…Since then, C. butyricum has been associated with botulism in other countries (i.e. China, India, Japan, Ireland, and the USA) [32]. Notably, the operon encoding the BoNT/E toxin harboured by the neurotoxigenic C. butyricum strains is very similar to that carried by group II type E toxin-producing C. botulinum strains [33].…”
Section: Pathogenic Botulismmentioning
confidence: 98%
“…Botulism is an acute paralytic disease caused by botulinum neurotoxin (BoNT), which is most frequently secreted by Clostridium botulinum [6]. Botulism can occur when BoNTproducing clostridia colonize wounds or the intestine and subsequently secrete the toxin, or when contaminated food is ingested (foodborne) [32]. In 1986, the first infant botulism case caused by a BoNT/E-producing C. butyricum strain was reported in Italy [6].…”
Section: Pathogenic Botulismmentioning
confidence: 99%
“…Foodborne botulism outbreaks involving Group II BoNT E have been frequently associated with the consumption of fish and fish products [6,7], probably due to temperature abuse as this group of bacteria is psychrotrophic and grows well in anaerobic, chilled environments [4,6]. While C. botulinum is the most common species producing botulinum neurotoxins, rare cases of BoNT E have been caused by C. butyricum [8].…”
Section: Disease Background Informationmentioning
confidence: 99%
“…Neurotoxigenic C. butyricum type E strains have been isolated from cases of intestinal toxemia botulism in infants and adults in Italy, Japan, USA, Ireland, and UK ( Aureli et al, 1986 ; Fenicia et al, 1999 , 2002 ; Abe et al, 2008 ; Dykes et al, 2015 ; Shelley et al, 2015 ); foodborne botulism cases in China, India and Italy ( Meng et al, 1997 ; Chaudhry et al, 1998 ; Anniballi et al, 2002 ); food and environmental samples (soil and lake shore) in China ( Meng et al, 1997 , 1999 ); and, more recently, from pets (turtles) which were identified as the likely source of infection in two infant botulism cases in Ireland ( Shelley et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%